Immigrants' experiences of the importance and value of work in Norway: Implications for social work - Reidun Ims (Social Work and Society, 2022)
In Norway, integration of immigrants through gainful employment is a prevailing idea in integrational measures. There is, however, a lack of knowledge on immigrants' lived experiences on the issue of work. This study examines how immigrants experience the importance of work, and how they perceive the value of work. Data were collected by nine qualitative semi-structured interviews with ten immigrants and underwent an interpretative phenomenological analysis. The findings provide the field of social work with important knowledge pertinent for professional practice. The participants considered work to be important and valuable. To the participants working represented self-sufficiency as well as financial independence. They linked work with a positive identity in society as they believed they were perceived positively by native Norwegians when they had regular work. Participants who obtained education prior to arriving in Norway had a wider variety of options when searching for work compared to those who lacked formal credentials.